(untitled) (CIPEEX, 2022)
INTRODUCTION: SEPSIS IS DEFINED BY THE PRESENCE OF LIFE-THREATENING ORGANIC DYSFUNCTION SECONDARY DUE TO THE HOST’S DYSREGULATED RESPONSE TO INFECTION. CONCERNING THIS DISEASE, MORTALITY REACHES ALARMING NUMBERS, AFFECTING 25% OF THE PATIENTS. THUS, THE ENHANCING OF EDUCATIONAL PRACTICES TO THE PROFESSIONAL WORK-TEAM SEEMS TO BE OF VITAL IMPORTANCE. THIS STUDY AIMS TO EVALUATE THE USE OF THE SEPSIS PROTOCOL IN A HOSPITAL OF MEDIUM-SIZE UNIT. METHOD: THE METHODOLOGICAL STRUCTURE IS BASED IN A CROSS-SECTIONAL, DESCRIPTIVE AND QUANTITATIVE STUDY. A TOTAL OF 441 SEPSIS PROTOCOL RECORDS WERE ANALYZED IN THE PERIOD COMPRISED FROM AUGUST/2016 TO MAY / 2017. RESULTS: CONSIDERING THE SAMPLE OF PATIENTS STUDIED, THE FEMALE GENDER PREVAILED (58%) THE OCCURRENCE OF THE DISEASE, AND THE RANGE AGE RESEARCHED COMPRISES THE AGE FROM 13 TO 109 YEARS OLD. IT IS IMPORTANT TO HIGHLIGHT THAT THE NURSE TEAM WAS PRESENT IN 7.5% OF THE PROTOCOL OPENINGS. THE MOST FREQUENT WARNING SIGN OF THE OCCURRENCE OF THE SEPSIS IS THE HEART RATE>90 BPM (N=335). SEVERAL REGISTERS WERE IGNORED: THE DIAGNOSIS OF SEPSIS AND THE DESTINATION OF THE PATIENT. CONCLUSION: SEPSIS DISEASE DEMANDS AN EXTREMELY HIGH COST TREATMENT, WHILE IT REGISTERS LOW SURVIVAL RATES. THE USE OF SEPSIS PROTOCOLS COMES TO PROVIDE QUALITY CARE AND EARLY RECOGNITION OF SEPSIS, THUS MINIMIZING PATIENT MORTALITY. SO, THE NURSE IS THE PROFESSIONAL WITH GREAT RESPONSIBILITY FOR IDENTIFYING AND UNDERSTANDING THE CLINICAL MANIFESTATIONS CAUSED BY SEPSIS. THEREFORE, THE CARE PLAN FOCUSING THE ATTENUATION OF SEPSIS IS EXTREMELY NECESSARY.